Morphology is dead – long live morphology! Integrating MorphoEvoDevo into molecular EvoDevo and phylogenomics - Wanninger, Andreas (Frontiers in Ecology and Evolution, 2015)
Morphology, the description and analysis of organismal form, is one of the oldest biological disciplines that has significantly contributed to our understanding as to how animals function and how the overwhelming diversity of phenotypes evolved. The early discovery that comparative studies of morphogenesis add to our understanding of the evolutionary history and interrelationships of organisms led to the formulation of highly influential evolutionary principles, including Haeckel’s theory of recapitulation or Hatschek’s trochozoon-hypothesis, and established the intellectual foundation of a research area today termed EvoDevo. While the rapid integration of molecular techniques into systematics, phylogenetics, and developmental biology from the 1980s onwards made some consider morphology as having little to contribute to evolutionary research, methodological progress together with a revived focus on morphogenesis has resulted in an unexpected renaissance of evolutionary developmental morphology, here termed MorphoEvoDevo. Herein, I briefly summarize some classical landmark contributions and progress achieved by studies using the MorphoEvoDevo approach. I will focus on the role of morphology in modern evolutionary biology, especially with respect to the molecular-driven approaches such as phylogenetics and developmental genetics. I argue that, while MorphoEvoDevo may well survive as an independent field of research, in times of increased competition for funding it will significantly profit from integration of the molecular disciplines into research programs with a strong emphasis on morphology. After all, morphological data are indispensable for reconstruction of phenotypic ground patterns and character evolution, and only a holistic approach incorporating all major subdisciplines of the evolutionary biosciences may ultimately result in a deep understanding, from molecules to ecosystems, of the driving forces that have shaped our organismal world.